Mass mediations : new approaches to popular culture in the Middle East and beyond - Armbrust, Walter (University of California Press, 2000)
Offering a stimulating diversity of perspectives, this collection examines how popular culture through mass media defines the scale and character of social interaction in the Middle East. The contributors approach popular culture broadly, with an interest in how it creates new scales of communication and new dimensions of identity that affect economics, politics, aesthetics, and performance.